FEATURES OF THE CLINICAL COURSE, OBSERVATION AND PREVENTION OF ADENOVIRAL EPIDEMIC KERATOCONJUNCTIVITIS IN INFANT IN THE PERINATAL CENTER - I. B. Astasheva (LLC "Diagnostics and Vaccines", 2017)
In recent years, the number of adenoviral epidemic keratoconjunctivitis (EKC) cases in a neonatal intensive care unit (NICU) has increased, which is primarily due to the establishment of an ophthalmologic service in these institutions, and the increase of the number of ophthalmologic examinations and manipulations.To characterize the features of the course and to identify the most effective methods of preventing adenoviral EKC of children during the first months of life who are on care and treatment in NICU. Adenoviral EKC is diagnosed in 284 children aged from 2 days to 3 months, who are on nursing in perinatal centers of Moscow. In 165 children with EKC retinopathy of prematurity (ROP) was noted. The course of adenoviral EKC in children in the age of the first months was accompanied by eyelids edema and conjunctiva edema, the formation of membranes (49.3%), hemorrhages (69.7%), corneal edema (30.3%), and absence of folliculosis of the eyelid conjunctiva. Cornea infiltrates occurred in 1.9% of cases and always disappeared in 1-2 weeks. after appearance. The development of adenoviral EKC in premature infants against the background of ROP complicates its course. Carrying out laser coagulation in children with ROP against the background of adenoviral EKC is safe and causes the same effect as in children without conjunctivitis. Conducting cryocoagulation at the peak of the conjunctivitis course is ineffective. Adherence to measures of the prevention of adenoviral EKC reduced the duration of the outburst to 1 month.The course of adenoviral EKC of children during the first months of life is severe, but in the end, no one child had any complications (long-term corneal infiltrates, conjunctivitis adhesions).